Projected expansion in two influenza-susceptible birds' distribution under climate and land-cover changes on the Qinghai-Tibetan Plateau - Xuelei Wei; Yunrui Ji; Ru Jia; Quanliang Li; Cunxin Ma; Xikang Song; Fangwei Cheng; Hengqing Yin; Fengyi Xu; Hongyan Yu; Ge Sun; Xiulei Wang; et al. (Global Ecology and Conservation)
Avian influenza is a global zoonotic disease influencing bird conservation and public health. Climate and land-cover changes can significantly impact influenza-susceptible species' distribution, thereby influencing avian influenza outbreaks. The Qinghai-Tibetan Plateau (QTP) plays a crucial role in avian influenza virus transmission and is susceptible to environmental changes. Here, we focused on two influenza-susceptible birds, the bar-headed goose (Anser indicus) and brown-headed gull (Chroicocephalus brunnicephalus), to predict their distribution on the QTP under climate and land-cover change scenarios. We integrated satellite tracking, field surveys, and publicly available datasets to collect species occurrence. Then, we utilized Biomod models to predict bird distribution under current and future scenarios. Our results indicated that the distance to water bodies (DW) and the mean temperature of the wettest quarter (BIO 8) significantly influenced the distribution of bar-headed geese and brown-headed gulls. The highly suitable distributions of both species are concentrated in the northeastern QTP and the Changtang Plateau, with only the Qaidam Basin showing a decrease in the future. Their future distribution has roughly doubled, with expansions toward western and higher elevations. We highlighted the influence of climate and land cover changes on bird distribution, and identified key areas of bird distribution, which are also critical areas for future avian influenza monitoring and prevention.